Macroscopic Modeling of Plant Water Uptake in a Forest Stand Involving Root‐Mediated Soil Water Redistribution. Issue 1 (15th February 2013) - Vogel, Tomas; Dohnal, Michal; Dusek, Jaromir; Votrubova, Jana; Tesar, Miroslav
Abstract : One of the principal components of mass exchange within the soil−plant−atmosphere system is soil water extraction by plant roots. Adequate evaluation of water extraction is a prerequisite for correct predictions of plant transpiration and soil water distribution in the root zone. The main objective of the present study is to contribute to the development of sufficiently realistic, yet algorithmically simple models of water exchange between soil and plant roots applicable for numerical simulation of soil water responses to atmospheric forcing. In our case, a simple macroscopic, vertically distributed plant root water uptake approximation based on a traditional water‐potential‐gradient (WPG) formulation was adopted and implemented in a one‐dimensional dual‐continuum model of soil water flow based on the Richards' equation. This combined model was used to simulate soil water movement at a forested site. The results were compared with observations (sap flow, soil water pressure, and soil water content) as well as with simulations produced using the standard semi‐empirical model of Feddes. Principal aspects of the WPG prediction, such as root‐mediated soil water redistribution, compensation for local water scarcity, and transpiration reduction, are exposed and discussed.